Analisis Teologis Pendampingan Pastoral Terhadap Kecanduan Gadget pada Anak Berdasarkan Amsal 22:6 - Santoso, Agung; Nainggolan, Bartolemeus Diaz (Institut Agama Kristen Negeri Palangka Raya, 2024)
This research comprehensively explores strategies for providing pastoral care and assistance to children who are addicted to gadgets. This approach uses in-depth analysis of the biblical text, especially Proverbs 22:6, and its application in the context of everyday life. The research methodology applied is a qualitative method and literature study and observation. Data was obtained through in-depth analysis of various literary sources including Biblical texts. The findings of this research firmly state that pastoral care and providing assistance to children who are addicted to gadgets is very important to free them from addiction. In addition, this research describes the dynamics of cultural and social changes that shape the perspective of this generation of children regarding the widespread use of gadgets, including in their free time. The theological implications of these findings provide a deep understanding of the needs and challenges faced by children in strengthening relationships with spiritual things in the modern era.